Noncoplanar Versus Coplanar Intensity-Modulated Radiation Therapy (IMRT) for Protection of the Lip and Buccal Mucosa. (27th May 2021) - Lao, Zheng; Bi, Fan; Fan, Wenhui; Xu, Xuanli; Tu, Wenyong; Shi, Huifeng
Objective: In this study, by comparing coplanar and noncoplanar intensity-modulated radiation therapy (IMRT) treatment planning in treating tongue cancer, the significance of noncoplanar fields in the protection of the lip and buccal mucosa was determined, and a reasonable solution was selected. Methods: Forty-eight tongue cancer patients treated from June 2019 to February 2021 were selected and randomly divided into a coplanar field group and a noncoplanar field group. The mucosal dose limit changed from 15 Gy to 45 Gy for comparison of the two treatment plans. The evaluation indicators (conformal index (CI); homogeneity index (HI); D5, D50, and D98 of the target volume; and the dose of normal tissues) were calculated under different mucosal dose limits. The clinical observation of the lip and buccal mucosa of 48 cases was monitored and graded carefully according to NCI-CTCAE V4.0. Statistical analyses were performed. Results: The differences in CI, HI, D98, D50 and D5 between the two groups in the target volume tended to decrease when the mucosal dose limit was less than 30 Gy, with a significant difference ( P < 0.05). When the limit exceeded 30 Gy, significant differences in other indicators except CI ( P < 0.05) were still noted. In normal tissue, differences in doses between the two groups existed when the mucosal limit was less than 20 Gy, with a significant difference ( P < 0.05). When the limit exceeded 20 Gy, no significant difference was noted. Patients in the noncoplanar group showed significantly better results than those in the other group in terms of the radiation-related toxicity of the lip and cheek membrane( P < 0.001). Conclusions: Compared with coplanar field radiotherapy, noncoplanar field radiotherapy can effectively reduce the exposure dose to the lip and buccal mucosa. The application of noncoplanar treatment plans exhibits good clinical significance and deserves to be promoted.